Nutritional management of food allergies: Prevention and treatment - Ludovica Leone; Alessandra Mazzocchi; Laura Maffeis; Valentina De Cosmi; Carlo Agostoni; Carlo Agostoni (Frontiers in Allergy, 2023)
An individualized allergen avoidance plan is the cornerstone of the nutritional management of food allergy (FA). In pediatric age, the main objective is preventing the occurrence of acute and chronic symptoms by avoiding the offending food(s) and providing an adequate, nutritionally balanced and personalized diet at the same time. For this reason, the presence of a trained dietitian is recommended in order to meet nutritional needs of patients with FA and to provide a tailored nutritional plan, minimizing the impact of FA on quality of life and maintaining optimal growth.